Dimensions of self-reported listening effort and fatigue on a digits-in-noise task, and association with baseline pupil size and performance accuracy. - Alhanbali, Sara; Munro, Kevin J.; Dawes, Piers; Carolan, Peter J.; Millman, Rebecca E. (International Journal of Audiology, 2021)
Pupillometry is sensitive to cognitive resource allocation and has been used as a potential measure of listening-related effort and fatigue. We investigated associations between peak pupil diameter, pre-stimulus pupil diameter, performance on a listening task, and the dimensionality of self-reported outcomes (task-related listening effort and fatigue). Pupillometry was recorded while participants performed a speech-in-noise task. Participants rated their experience of listening effort and fatigue using the NASA-Task Load Index (NASA-TLX) and the Visual Analogue Scale of Fatigue (VAS-F), respectively. The dimensionality of the NASA-TLX and the VAS-F was investigated using factor analysis. 82 participants with either normal hearing or aided hearing impairment (age range: 55–85 years old, 43 male). Hierarchal linear regression analyses suggested that pre-stimulus pupil diameter predicts a dimension of self-reported fatigue, which we interpreted as tiredness/drowsiness, and listening task performance when controlling for hearing level and age: Larger pre-stimulus pupil diameter was associated with less tiredness/drowsiness and better task performance. Pre-stimulus pupil diameter is a potential index of listening fatigue associated with speech processing in challenging listening conditions. To our knowledge, this is the first investigation of the associations between pre-stimulus pupil diameter and self-reported ratings of listening effort and fatigue.